USER INTERFACE AND USER EXPERIENCE OF INDOSPORT MOBILE APPLICATIONS USING A USER CENTERED DESIGN APPROACH - Fadli, Muhammad Raffi (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
An alternative solution for Indosport, considering the increasingly advanced smartphone development and also followed by the rapid growth of its users in Indonesia. The purpose of this study project is to produce a product in the form of a user interface (UI) and user experience (UX) design in helping to realize targeted mobile applications and not forgetting to apply the principles of visual communication design namely unity and variety, hierarchy, contrast, proportion and balance. The UI and UX design methods go through several stages of work in sequence: pre-production process, production process, and post-production. This design results in UI and UX designs that are equipped with user flow, interface designs, illustrations and prototypes. The main page of the Indosport mobile application is News, Activity, Calendar, and Profile which later on these pages there are several features that are different from the previous page. The making of this UI uses several visual languages such as medium close up, full shot, long shot, close up and medium long shot in the image section contained in the article as well as the depiction of field styles used to almost all visual UI elements. Using several principles in design, namely time to learn, speed of performance, rate of errors by users, retention over time, and subjective satisfaction. The resulting design forms will be distributed directly to the Research and Development division and the IT division from Indosport to be made a native.